2015
DOI: 10.1017/jmo.2015.38
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high-performance work systems on firm performance: The moderating effects of the human resource function’s influence

Abstract: With data collected from 632 manufacturing firms in South Korea, we investigated (1) the relationship between high-performance work systems (HPWSs) and firm performance, and (2) the moderating effect of the human resource (HR) function’s influence on the relationship between HPWSs and firm performance. Our findings showed the existence of both the main effect of HPWSs, supporting the universalistic perspective, and the moderating effect of the HR function’s influence, supporting the contingency perspective. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 125 publications
(225 reference statements)
1
19
0
1
Order By: Relevance
“…This consistency suggests that HRM is part of a cohesive and structured work environment. Lockett, Thompson, and Morgenstern (2009) posit that managers fail to understand the potential of the resources at their disposal, therefore emphasising the centrality of HRM expertise and their role in resource optimisation to further the strategic goals of the organisation (Jeong & Choi, 2016).…”
mentioning
confidence: 99%
“…This consistency suggests that HRM is part of a cohesive and structured work environment. Lockett, Thompson, and Morgenstern (2009) posit that managers fail to understand the potential of the resources at their disposal, therefore emphasising the centrality of HRM expertise and their role in resource optimisation to further the strategic goals of the organisation (Jeong & Choi, 2016).…”
mentioning
confidence: 99%
“…Secondly, the universal approach may be effective in many cases (Zhang and Morris, 2014;Jeong and Choi, 2016). However, this research shows that when aspects of HRM practices do not fit with the types of organizational cultures, organizational performance will be negatively affected.…”
Section: Theorethical Implicationsmentioning
confidence: 84%
“…Batt (2000) showed greater benefits from HIWPs among employees working with higher valued-added customers. Combs et al (2006) observed a higher impact of HIWPs in manufacturing than in service firms, and Jeong and Choi (2016) highlighted that the presence of an influential HR function can intensify the effect of HPWSs on firm performance.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…This approach assumes that firms that achieve the best fit between the two types of variable – HR practices and contextual or contingency factors – will obtain better performance. Although the two approaches seem contradictory, it has also been argued that both have merit, that they may be complementary (Jeong & Choi, 2016) and that organizations benefit from attention to each (Rau, 2012). Youndt, Snell, Dean, and Lepak (1996) sustain that the universalistic approach helps researchers to document the benefits of HRM in any context, ceteris paribus , whereas the contingency approach allows them to carry out more in-depth analysis of organizational phenomena, facilitating the development of more specific theories on HRM from the contextual point of view, and allowing more precise findings on the use of HR practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation